A new species and a key to world species of the flavipes species-group of the genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) from Japan - Fujie, Shunpei; Shimizu, So; Fernandez-Triana, Jose (Zootaxa, 2018)
A new species of microgastrine parasitoid wasp (Hymenoptera: Braconidae), Cotesia testacea Fujie, Shimizu & Fernandez-Triana sp. nov., is described from Japan and Korea. It belongs to the flavipes species-group, which now comprises seven described species, most of them economically important as biocontrol agents of cereal and sugarcane stem borer pests worldwide. The new species, currently known from marsh habitats in the Eastern Palaearctic, is morphologically similar and probably related to the Western Palaearctic Cotesia ferruginea. A key to world species of the flavipes species-group is also provided.